2016
DOI: 10.1038/eye.2016.159
|View full text |Cite
|
Sign up to set email alerts
|

Congenital cataract associated with persistent fetal vasculature: findings from IoLunder2

Abstract: Purpose To describe the frequency, characteristics, and treatment outcome of persistent fetal vasculature (PFV) in children undergoing surgery for congenital and infantile cataract in the first 2 years of life. Patients and methods Observational population-based cohort study with case identification through active surveillance and standardised data collection via a national clinical network, the British Isles Congenital Cataract Interest Group (BCCIG). Results The IoLunder2 cohort comprises 246 children underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
17
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 17 publications
4
17
1
4
Order By: Relevance
“…[211] In a study reported by Solebo et al , they have observed the incidence of PFV to be 24% in children with congenital cataract, out of which 46% had unilateral and 8% had bilateral cataract. [12] Age of presentation in our study was ranging from 3 months to 132 months (mean: 41.15 months), which is corresponding to the study done by Mullner-Eidenbock A et al who reported age of presentation ranging from 2 weeks to 15 years in 31 cases of unilateral cataract with PFV. [13] This wide range of age at presentation can be attributed to the fact that all the cases in our study had unilateral cataract with PFV which is likely to go unnoticed because of the normal functioning other eye.…”
Section: Discussionsupporting
confidence: 86%
“…[211] In a study reported by Solebo et al , they have observed the incidence of PFV to be 24% in children with congenital cataract, out of which 46% had unilateral and 8% had bilateral cataract. [12] Age of presentation in our study was ranging from 3 months to 132 months (mean: 41.15 months), which is corresponding to the study done by Mullner-Eidenbock A et al who reported age of presentation ranging from 2 weeks to 15 years in 31 cases of unilateral cataract with PFV. [13] This wide range of age at presentation can be attributed to the fact that all the cases in our study had unilateral cataract with PFV which is likely to go unnoticed because of the normal functioning other eye.…”
Section: Discussionsupporting
confidence: 86%
“…The IoLunder 2 cohort study also did not find an association between cataract type and the development of glaucoma. 8 …”
Section: Discussionmentioning
confidence: 99%
“…Pediatric cataract management has gained tremendous focus in the past decade. [ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 ] There is a renewed sense that while cataract surgery in adults appears to be evolving at a furious pace that pediatric cataract surgery is perhaps lagging in our understanding of the basic physiological and anatomical issues that play a role in a successful outcome.…”
mentioning
confidence: 99%
“…It is, in fact, the bilateral dense cataracts in children that are of greater developmental concern; evidence from a large longitudinal cohort study from the UK suggests that bilateral pseudophakia may result in better visual outcomes. [ 5 ] Why should this be ? Well most cases of unilateral cataracts are due to some form of PHPV with an eye that is usually smaller than the unaffected eye.…”
mentioning
confidence: 99%
See 1 more Smart Citation